Self-Esteem among University Students: How It Can Be Improved through Teamwork Skills - Elena De Prada; Mercedes Mareque; Margarita Pino-Juste (MDPI AG, 2024)
Teamwork skills have been demonstrated to be excellent allies for the academic and professional sphere, and they can improve students' psychological balance and self-esteem. For this reason, it is important to explore the relationship between teamwork skills and self-esteem. Considering the relevance of soft skills and self-esteem in university training, the main objective of this study is to determine whether there is a relationship between teamwork skills and the successful development of self-esteem, a fundamental emotional factor in education. Additionally, we will analyse how self-esteem is related to other socio-academic factors (age, sex, and GPA). A questionnaire was distributed to social science university students. The Rosenberg 10-item scale, which aims to measure feelings of personal worth and self-respect, has been used to determine self-esteem. To measure soft skills for teamwork, we chose the Teamwork Skills Questionnaire, which evaluates the skill level of an individual in order to participate effectively in teamwork. The regression model indicates that self-esteem predictors related to teamwork skills are decision making, leadership, and communication. The results suggest significant differences in some individual variables, such as sex and age, with lower self-esteem being observed in females and older students. The described enriching interactions suggest the need to integrate teamwork training and self-esteem fostering at university to offer students lifelong competencies for their future success.